Omics-Based Mechanistic Insight Into the Role of Bioengineered Nanoparticles for Biotic Stress Amelioration by Modulating Plant Metabolic Pathways - Kumari, Madhuree; Pandey, Shipra; Mishra, Shashank Kumar; Giri, Ved Prakash; Agarwal, Lalit; Dwivedi, Sanjay; Pandey, Alok Kumar; Nautiyal, Chandra Shekhar; Mishra, Aradhana (Frontiers in Bioengineering and Biotechnology, 2020)
Bioengineered silver nanoparticles can emerge as a facile approach to combat plant pathogen reducing the use of pesticides in an eco-friendly manner. The plants responses during tripartite interaction of plant- pathogen, and nanoparticles remain largely unknown. This study demonstrated the use of bioengineered silver nanoparticles in combating black spot disease caused by necrotrophic fungus Alternaria brassicicola in Arabidopsis thaliana via foliar spray. The particles reduced disease severity by 70-80% at 5µg/mL without showing phytotoxicity. It elicited plant immunity by a significant reduction in reactive oxygen species (ROS), decreases in stress enzymes by 0.6-19.8 folds and emergence of autophagy. Comparative plant proteomics revealed 599 proteins expressed during the interaction, where 117 differential proteins were identified. Among different categories, proteins involved in bioenergy and metabolism were most abundant (44%), followed by proteins involved in plant defence (20%). Metabolic profiling by Gas Chromatography-Mass Spectroscopy yielded 39 metabolite derivatives in non-polar fraction, and 25 in polar fraction of plant extracts. It was observed that proteins involved in protein biogenesis and early plant defence were overexpressed to produce abundant antimicrobial metabolites and minimize ROS production. Bioengineered silver nanoparticles performed dual functions to combat pathogen attack by killing plant pathogen and eliciting immunity by altering plant defence proteome and metabolome.